(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2023)
Biosurfactants are microbial amphiphilic compounds, which can reduce surface tension between two immiscible liquids. Indigenous microbes isolated from raw unprocessed cow’s milk were characterized morphologically and biochemically. The biosurfactant-producing ability of the isolates was determined by hemolytic activity, oil displacement technique and their emulsification activity which screened against oil. Biosurfactants were produced and those were tested for their antibacterial activities against various bacterial strains. Then the biosurfactants were added to milk samples for analysing the shelf life of raw unprocessed cow’s milk. The effect of biosurfactants on raw milk is analyzed by visual and microbial enumeration. In this study, 8 indigenous microbes were isolated from raw milk. The best isolates for biosurfactant production were identified as Bacillus sp., and Lactobacillus sp., based on screening assays. The biosurfactant extracted from these screened isolates exhibited antimicrobial activity against infectious agents. Moreover, they showed its effect on the potential enhancement of the shelf life of raw milk. Isolated and screened microflora can be a good source of biosurfactant and they are proven to be a beneficial means for large and small-scale industries to supply good quality milk.